Carpal Tunnel Syndrome - Ryan Valensky; Hendra Kastiaji (Pusat Riset dan Inovasi Nasional, 2026)
Carpal tunnel syndrome (CTS) is a collection of symptoms caused by compression of the median nerve, resulting in increased pressure within the carpal tunnel at the wrist. The highest prevalence, reaching 61%, occurs among industrial workers, particularly those who use grinding tools, whereas the prevalence is approximately 1% among individuals who rarely perform repetitive hand movements. Risk factors for CTS include repetitive use of the hands and wrists, poor posture, heavy lifting, and exposure to vibration, as well as obesity, female sex, advanced age, and smoking. Carpal tunnel syndrome presents with a range of characteristic symptoms, varying from moderate pain to severe pain. As the condition progresses, patients diagnosed with CTS commonly complain of numbness, tingling, and burning sensations in the thumb, index finger, middle finger, and the radial half of the ring finger, as these digits are innervated by the median nerve. Management of CTS is determined by disease severity. Conservative treatment is recommended for mild to moderate cases, whereas patients with severe CTS or evidence of nerve damage on electrodiagnostic examination require surgical decompression.